Book Review of Managing Globalization in the Asian Century : Essays in Honour of Prema-Chandra Athukorala - Rahardja, Sjamsu (Taylor and Francis, 2018)
Asia is a region of economic miracles, and this festschrift for the esteemed development economist Prema-Chandra Athukorala highlights a major driver of Asia’s success: globalization. Economic progress in Asia cannot be separated from globalization’s role in industrializing the region’s agrarian economies. Most countries in Asia have, to varying degrees, embraced globalization by opening up to foreign direct investment (to stimulate markets and to transfer know-how) and facilitating the growth of export-oriented industries.